A271 THE HELICOBACTER PYLORI VACA TOXIN IMPAIRS LYSOSOMAL CALCIUM CHANNEL TRPML1 ACTIVITY TO PROMOTE COLONIZATION. (1st March 2018) - Capurro, M; Greenfield, L; Wong, H; Robinson, L; Jones, N
Abstract: Background: Helicobacter pylori ( H. pylori ) is a proven carcinogen for gastric cancer. The vacuolating cytotoxin A (VacA) is a bacterial virulence factor that promotes more severe disease and gastric colonization. VacA generates a unique reservoir for H. pylori within gastric cells conferring bacterial survival advantage. Normally the lysosome and autophagy pathways target and eliminate intracellular pathogens. VacA disrupts the endolysosomal pathway to form large intracellular vacuoles and impairs host-cell autophagy to generate the intracellular niche. However, the mechanism by which VacA alters the endolysosomal pathway is unknown. Proper vesicular trafficking, lysosomal biogenesis and autophagy pathway require a functional Mucolipin Transient Receptor Membrane Calcium channel 1 (TRPML1). Interestingly, TRPML1 deficient cells display enlarged vacuoles and disrupted autophagy, as observed in VacA-treated cells. Furthermore, TRPML1 deficient mice display hypergastrinemia and hypochlorhydria, conditions observed during H. pylori infections. Aims: Hypothesis : We hypothesized that VacA inhibits TRPML1 to promote an intracellular niche. Methods: We employed gastric cells, murine wild type and trpml1 -/- and human organoid models as well as in vivo murine infection in wild type and trpml1 -/- mice using VacA+ and isogenic VacA mutant H. pylori . Results: We found elevated intraluminal lysosomal calcium levels in VacA-treated gastric adenocarcinoma (AGS) cells consistent with disrupted TRPML1 activity. Furthermore, using a small molecule agonist to activate TRPML1 in VacA + H. pylori -infected human gastric cell lines and organoids restores normal lysosomal and autophagic function, eliminating the intracellular protective niche and resulting in efficient bacterial killing. Consistent with these observations, we found that VacA+ H. pylori infected mice displayed intracellular bacteria in parietal cells. Similarly, the enlarged lysosomal-like vacuoles present in the parietal cells of trpml1 -null mice were colonized by mutant VacA - H. pylori . Conclusions: Altogether, we identify TRPML1 as a target that VacA exploits to evade host killing. We provide initial evidence that TRPML1 could serve as the first non-bacterial target to kill intracellular H. pylori . In this era of increasing antibiotic resistance and urgent need for research and development of new antimicrobials, we expect that TRPML1 agonists could be explored as novel therapies against intracellular pathogens. Funding Agencies: CAG, CIHR